THE IMPROVEMENT OF INDUCTION AND CONSIDERATE INDUCTION RESULT SKILL BY THE PROBLEM SOLVING LEARNING - Malida Aprilliza; ratu betta rudibyani; tasviri efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
The objective of this research is to know effectiveness of problem solving learning in improving skill induct and considerate induction result . Population was 360 students of Grade X State Senior High School 12 in Bandar Lampung. Samples were X1 and X3 classroom. Every class has 38 students that have equal academic abilities. This was a quasi experiment research using non equivalent control group design. Effectiveness of problem solving learning was measured based on significant n-Gain improvements of showing the general thing and making conclution and hypotesis skill. The both are subindicator of  induction and considerate induction result. The results showed that average value of n-Gain of showing the general thing skill in experiment and control classrooms were 0.4 and 0.28 respectively; and average value of n-Gain for making conclution and hypotesis in experiment and control classrooms were 0.36 and 0.20 respectively. The result showed that classroom that used problem solving had higher induct and considerate result induction skill than classroom with conventional learning. This indicated that problem solving learning was effective to improve student’s induction and considerate induction result skill mastery of the concept at basic laws of chemistry.Keywords: Problem Solving, induction and considerate induction result skill